Preparing Specialized Arab Hospital –Nablus for ISO 50001:2011 - Shanabli, Waseem; Sayeh, Zaid; Othman, Omar; Amer, Nidal; Ghannam, Lana (My University, 2016)
Project Name: Developing an Energy Management System (ISO 50001) at Specialized Arab Hospital –Nablus. Academic Year: 2015/2016 Department Names: Energy Engineering and Environment Problem Statement: The high energy bills and fuel requirements have always been a major concern for the Specialized Arab Hospital. Demand on energy is continuously increasing. In order to overcome this problem, the Energy Consumptions Systems at the hospital were subjected to the terms of the ISO 50001:2011 standard in Energy Management which is issued by the International Organization for Standardization ISO. Energy Management considers reducing the release of CO2 and Greenhouse gases by limiting and reducing the needed energy in the hospital. These gases are known to be the main reason of global warming. Since ISO 50001:2011 is related to energy management, implementing its standards can greatly affect the global warming in a positive way. ISO 50001:2011 specifies requirements for establishing, implementing, maintaining and improving an energy management system, that aims to enable organizations to follow a systematic approach in achieving continual improvement of energy performance, including energy efficiency, energy use and consumption. Many parameters are involved in the conduction of standardization process. These parameters include measurements, documentation, reporting, designing, procurement practices for equipment and systems, processes and personnel and others. All of these contribute to develop energy performance. The parameters can vary, change or be influenced by the hospital policy and management. Project Description In this project, the Specialized Arab Hospital -Nablus was prepared to comply with the requirements of the ISO 50001:2011. Energy Management approaches were implemented and improved in all of considerable energy consumption systems. The main studied systems were lighting, boilers, the chiller, air conditioners, Oxygen station, elevators and laundry. The characteristics, electricity and gas consumption of these systems were analyzed. Documentation methodology was improved. And finally recommendations were set.